If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 2(x^{2}) + -7x = 1 Reorder the terms: -7x + 2x^{2}= 1 Solving -7x + 2x^{2}= 1 Solving for variable 'x'. Reorder the terms: -1 + -7x + 2x^{2}= 1 + -1 Combine like terms: 1 + -1 = 0 -1 + -7x + 2x^{2}= 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. -0.5 + -3.5x + x^{2}= 0 Move the constant term to the right: Add '0.5' to each side of the equation. -0.5 + -3.5x + 0.5 + x^{2}= 0 + 0.5 Reorder the terms: -0.5 + 0.5 + -3.5x + x^{2}= 0 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + -3.5x + x^{2}= 0 + 0.5 -3.5x + x^{2}= 0 + 0.5 Combine like terms: 0 + 0.5 = 0.5 -3.5x + x^{2}= 0.5 The x term is -3.5x. Take half its coefficient (-1.75). Square it (3.0625) and add it to both sides. Add '3.0625' to each side of the equation. -3.5x + 3.0625 + x^{2}= 0.5 + 3.0625 Reorder the terms: 3.0625 + -3.5x + x^{2}= 0.5 + 3.0625 Combine like terms: 0.5 + 3.0625 = 3.5625 3.0625 + -3.5x + x^{2}= 3.5625 Factor a perfect square on the left side: (x + -1.75)(x + -1.75) = 3.5625 Calculate the square root of the right side: 1.887458609 Break this problem into two subproblems by setting (x + -1.75) equal to 1.887458609 and -1.887458609.## Subproblem 1

x + -1.75 = 1.887458609 Simplifying x + -1.75 = 1.887458609 Reorder the terms: -1.75 + x = 1.887458609 Solving -1.75 + x = 1.887458609 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.75' to each side of the equation. -1.75 + 1.75 + x = 1.887458609 + 1.75 Combine like terms: -1.75 + 1.75 = 0.00 0.00 + x = 1.887458609 + 1.75 x = 1.887458609 + 1.75 Combine like terms: 1.887458609 + 1.75 = 3.637458609 x = 3.637458609 Simplifying x = 3.637458609## Subproblem 2

x + -1.75 = -1.887458609 Simplifying x + -1.75 = -1.887458609 Reorder the terms: -1.75 + x = -1.887458609 Solving -1.75 + x = -1.887458609 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.75' to each side of the equation. -1.75 + 1.75 + x = -1.887458609 + 1.75 Combine like terms: -1.75 + 1.75 = 0.00 0.00 + x = -1.887458609 + 1.75 x = -1.887458609 + 1.75 Combine like terms: -1.887458609 + 1.75 = -0.137458609 x = -0.137458609 Simplifying x = -0.137458609## Solution

The solution to the problem is based on the solutions from the subproblems. x = {3.637458609, -0.137458609}

| x^2+4x-2m=0 | | 27x^2-5x=0 | | 7e^8+t=2 | | 13x^2-28x=0 | | 15n+3n^4-4n+12n^4+n= | | 2x^2-24x=-2x^2-7x-18 | | 30x^3-9x^2-3x=0 | | x^2+4=17 | | (x^3+2x+3x+6)= | | (2x^3+3)= | | (x^2+3)(x^3+2x^2+3x+6)+(2x^3+3)= | | 10y^2+33y+20=0 | | y^3+8y^2+16y=0 | | x^2+4x-60=0 | | 14x^2-5x=0 | | (x^3+y^5)(x^3-y^5)= | | 5x^2+11x+1=0 | | y^2-16y-4= | | y=5x^2-3x+5 | | 7x-28=2x^2-8x-3x+12 | | y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions